Enhancing academic writing skills and motivation: assessing the efficacy of ChatGPT in AI-assisted language learning for EFL students - Song, Cuiping; Song, Yanping (Frontiers in Psychology, 2023)
This mixed methods study aimed to evaluate the effectiveness of AI-assisted language learning on the writing skills and writing motivation of Chinese English as a Foreign Language (EFL) students. Given the increasing presence of artificial intelligence (AI) in educational contexts, it is essential to understand its impact on language learning outcomes. The study employed a comprehensive approach by combining quantitative and qualitative methods. In the quantitative phase, a pre-test and post-test design was used to assess the students' writing skills. A total of fifty EFL students with similar proficiency levels were randomly assigned to either the experimental group, receiving AI-assisted writing instruction via ChatGPT, or the control group, receiving traditional writing instruction. Writing samples were evaluated using established scoring rubrics to measure writing performance. Concurrently, the qualitative phase involved conducting semi-structured interviews with a subset of participants to explore their writing motivation, perceptions, and experiences with AI-assisted language learning. The quantitative analysis revealed a significant improvement in the writing skills and writing motivation of the EFL students who received AI-assisted instruction compared to the control group. The experimental group demonstrated enhanced proficiency in various aspects of writing, including organization, coherence, grammar, and vocabulary. Moreover, the qualitative findings illuminated a spectrum of perspectives among students. These ranged from a recognition of AI's innovative role in instruction and its positive influence on writing skills, motivation, and engagement, to the acknowledgment of potential challenges in contextual accuracy and concerns about over-reliance. Additionally, participants reflected on the potential long-term impact and sustainability of AI-assisted writing instruction, underscoring the need for ongoing development and adaptation of AI tools. These nuanced themes offer a comprehensive understanding of the transformative potential of AI in education and provide valuable insights for practitioners and researchers alike.